Validating the decent work scale incorporated with a social recognition component among young adult social workers - Su, Xuebing; Wong, Victor; Liang, Kun (Frontiers in Psychology, 2022)
The decent work notion has sparkled a keen academic interest in studying the psychological influence of decent work on workers in organizational contexts. Duffy’s decent work notion has left a window for addressing the interpersonal barriers on or factors for enhancing people’s equal access to decent work, which may enhance the capacity of the decent work notion and the psychology of working theory to promote inclusiveness within the organizational context through leveraging the interpersonal mechanisms. Against this backdrop, a across-sectional study was conducted to validate a decent work scale incorporated with a social recognition component among young adult social workers aged 21–29 in Hong Kong (N = 362). The results of confirmatory factor analyses supported the six-factor-higher-order model of the decent work scale incorporated with a social recognition component. Decent work incorporated with social recognition correlated with job demands, job resources, and work engagement in the expected directions, and the results of average variance extracted analyses supported the discriminant validity of the decent work scale incorporated with social recognition. The value added by decent work in enhancing work engagement after controlling the effects of job resources justifies the concurrent validity of the concept. The expanded notion of decent work incorporated with the social recognition component is deemed applicable to informing further research and practice.